Firm Characteristics and Earnings Management Practices (EMP): Comparative Analysis in Sub-Saharan Africa - Saheed Akande, Shittu; Morufu Oladehinde, Oladejo; Folasade Foyeke, Peters; Babatunde Williams, Amao (INTI International University, 2024)
The study examines the influence of firms’ characteristics on accrual and real Earnings Management Practices (EMP). Firm characteristics include Asset Structure (AS), Capital Structure (CS), Dividend Payout Ratio (DPR), Firm Profitability (FP), Free Cash Flow (FCF), and Working Capital (WC). EMP was proxied by Discretionary Accrual (DA) and Real Earnings Management (REM). Two hundred and seventy-nine (279) non-financial listed firms with the data required for the study from 2010 to 2020 were selected from six (6) countries in sub-Saharan Africa. The study found that AS has a negative and significant influence on DA in Kenya and Tanzania. DPR positively and significantly influence DA in Zimbabwe and WC on DA in South Africa. Also, CS has a positive and significant impact on DA in Nigeria and DPR and CS on DA in Ghana. Also, AS and CS have a positive and significant impact on REM in Ghana. However, AS, FCF, DPR, FP, and WC have a negative and significant effect on REM in Nigeria. The study concludes that DA and REM significantly influence firm characteristics in sub-Saharan Africa. This study fills exiting gaps on EMP in Sub-Saharan Africa by considering the effect of firms’ characteristics on both DA and REM. The study expands knowledge on the importance of firm characteristics on EMP in sub-Saharan Africa regions where the majority of countries are developing nations and REM has not received adequate attention.